Mechanism and Prevention of Spiral Ganglion Neuron Degeneration in the Cochlea - Zhang, Li; Chen, Sen; Sun, Yu (Frontiers in Cellular Neuroscience, 2022)
Sensorineural hearing loss (SNHL) is one of the most prevalent sensory deficits in humans, and approximately 360 million people worldwide are affected. The current treatment option for severe to profound hearing loss is cochlear implantation (CI), but its treatment efficacy is related to the survival of spiral ganglion neurons (SGNs). SGNs are the primary sensory neurons, transmitting complex acoustic information from hair cells to second-order sensory neurons in the cochlear nucleus. In mammals, SGNs have very limited regeneration ability, and SGN loss causes irreversible hearing loss. In most cases of SNHL, SGN damage is the dominant pathogenesis and it could be caused by noise exposure, ototoxic drugs, hereditary defects, presbycusis, etc. Tremendous efforts have been made to identify novel treatments to prevent or reverse the damage to SGNs, including gene therapy and stem cell therapy. This review summarizes the major causes and the corresponding mechanisms of SGN loss and the current protection strategies, especially gene therapy and stem cell therapy, to promote the development of new therapeutic methods.